Discovery of Raltegravir, a potent, selective orally bioavailable HIV-integrase inhibitor for the treatment of HIV-AIDS infection - Summa, Vincenzo; Petrocchi, Alessia; Bonelli, Fabio; Crescenzi, Benedetta; Donghi, Monica; Ferrara, Marco; Fiore, Fabrizio; Gardelli, Cristina; Paz, Odalys Gonzalez; Hazuda, Daria J.; Jones, Philip; Kinzel, Olaf; et al. (Journal of medicinal chemistry, 2008)
Human immunodeficiency virus type-1 (HIV-1) integrase is one of the three virally encoded enzymes required for replication and therefore a rational target for chemotherapeutic intervention in the treatment of HIV-1 infection. We report here the discovery of Raltegravir, the first HIV-integrase inhibitor approved by FDA for the treatment of HIV infection. It derives from the evolution of 5,6-dihydroxypyrimidine-4-carboxamides and N-methyl-4-hydroxypyrimidinone-carboxamides, which exhibited potent inhibition of the HIV-integrase catalyzed strand transfer process. Structural modifications on these molecules were made in order to maximize potency as HIV-integrase inhibitors against the wild type virus, a selection of mutants, and optimize the selectivity, pharmacokinetic, and metabolic profiles in preclinical species. The good profile of Raltegravir has enabled its progression toward the end of phase III clinical trials for the treatment of HIV-1 infection and culminated with the FDA approval as the first HIV-integrase inhibitor for the treatment of HIV-1 infection.